Pelatihan Pembuatan Bubur California Untuk Mencegah Serangan Hama Tikus di Desa Setail Kecamatan Genteng: Peningkatan Kapasitas Petani dalam Mengendalikan Hama Tikus Melalui Penerapan Teknologi Bubur California (BC) di Desa Setail - Nadia Nisa; Dani Kurniawan; Annisa Salsabila Rosi; Sigit Prastowo (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Rodent infestations in rice fields have become a persistent and serious challenge for farmers in Desa Setail, Genteng, Banyuwangi. Various control methods such as the installation of owl house, the use of rodenticides, and fumigation have been applied, however, the results remain suboptimal. In response to this issue, KKN of the University of Jember 2025 collaborated with the Flamboyan Farmers’ Group and the Agricultural Extension Officer to introduce an innovative and environmentally friendly alternative known as Bubur California (BC). BC is a locally developed biopesticide formulated from sulfur and limestone, which has the potential to reduce rat populations while minimizing ecological risks compared to synthetic chemicals. The program was implemented through participatory learning approaches, including structured socialization sessions and hands-on demonstrations of BC production. These activities enabled farmers to directly engage in the process, thereby enhancing their technical skills and practical knowledge of sustainable pest management. The outcomes revealed strong enthusiasm among participants, reflected in active discussions and willingness to adopt BC in their farming practices. This initiative not only addressed the urgent problem of rat infestations but also promoted community empowerment by encouraging self-reliance and environmentally responsible agricultural practices. Consequently, the adoption of BC is expected to serve as a sustainable solution for rat pest management while simultaneously safeguarding environmental health and supporting long-term agricultural productivity in Setail Village.